Controlling factors of the climatological annual cycle of the surface mixed layer oxygen content: A global view - Wang, Zhankun; Garcia, Hernan E.; Boyer, Tim P.; Reagan, James; Cebrian, Just (Frontiers in Marine Science, 2022)
The annual cycle of global dissolved oxygen content (O2C) and mean oxygen concentration in the surface mixed layer are estimated using monthly climatological oxygen fields from the World Ocean Atlas 2018 (WOA18). The largest seasonal variability in the mixed layer O2C occurs in the extra-tropics between 30° and 70° latitude of each hemisphere. A global view of the role of entrainment, air-sea flux, and biological activity in controlling the oxygen content/concentration annual cycle in the mixed layer is determined using an oxygen mass balance model. Based on the relative percentage from the mass balance model, entrainment is only a significant driver (contributing to 20-40% of the total changes) from mid-fall to early spring when the mixed layer deepens and transfers oxygen to deeper waters. Both the air-sea oxygen flux and biological activity show strong annual cycles and play critical roles in the annual cycle of O2C in the mixed layer. Air-sea oxygen flux is ingassing from late fall to early spring and outgassing between late spring and early fall. It is a substantial factor throughout the year and controls 40-60% of the oxygen changes in most months. Biological activity is a net source (production) in the spring and summer and a net sink (consumption) in the late fall and winter for the mixed layer oxygen content. Biological activity plays a more important role during spring/summer (40-60%) than that during fall/winter (10-30%) in controlling the overall oxygen change in each month. The model estimates a mean value (±SD) of 3.06±1.61 mol C m-2 yr-1 and a total of 863.7±73.8 Tmol C yr-1 for the global annual net ocean community production (ANCP) between 60°S and 60°N latitude, which are in fairly good agreement with previous studies.